PERANCANGAN PHOTOBOOK UTILISASI SHORT AND LONG EXPOSURE UNTUK MENSIMULASIKAN GERAKAN PADA FOTO - Jimmy Pratama; Ji Cai (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2022)
In this modern era, visual arts are widely applied in our daily lives, ranging from posters, billboards, advertising, postings on social media, and so on. Photography is a medium that functions to channel work ideas to art connoisseurs. Exposure is used as a standard for comparing photos from various settings, but for a beginner, it is difficult to understand if only learned through words. At this stage of development, the visual of the essay book design must meet several stages in the design of the book. The following steps must be taken before developing an essay book design, Photoshoot, selection, designs, editing, layouts, exports, validation. In the photoshoot development method, the author will take several photos that will be sampled using short and long exposures. In the selection stage, the writer sorts out which images will be included in the design process and after that the writer does the editing by designing the layout and exporting it into a photobook which will be assessed by the beginners themselves